PENGARUH LITERASI KEUANGAN DAN FAKTOR DEMOGRAFI TERHADAP KEPUTUSAN PINJAMAN NASABAH KUR MIKRO DI PT. BRI UNIT PAGERAGEUNG - Adi Robith Setiana (Business Management and Entrepreneurship Journal, 2021)
This study aims to determine: 1). Customers Financial literacy of BRI Unit office Pagerageung. 2).Customers demographic factors of BRI Unit office Pagerageung. 3). The decision-making loans to customers BRI Unit office Pagerageung. 4). The Influence of financial literacy as well as demographic factors to the decision-making loans to customers BRI Unit office Pagerageung.The research method used in the research is descriptive quantitative method. Population in the research is all customers KUR Micro of BRI Unit office Pagerageung. Sample in this research counted 97 respondents. The data used in this research is primary data and secondary data. The analysis tools used are Interval Levels Value, uji asumsi klasik, kompleks regression analysis, and hypothesis test.The result of this study indicate that: 1). Financial literacy of BRI Unit office Pagerageung based on the views of customers included in the classification is good. 2). Demographic factors of BRI Unit office Pagerageung based on the views of customers included in the classification is good. 3). The desicion-making loans of BRI Unit office Pagerageung based on the views of customers included in the classification is good. 4). Financial literacy as well as demographic factors has significant influence to the decision-making loans to customers BRI Unit office Pagerageung. Keywords: financial literacy, demographic factors, the decision-making loans.